Long-term changes in adult size of green turtles at Aldabra Atoll and implications for clutch size, sexual dimorphism and growth rates - Mortimer, Jeanne A.; Appoo, Jennifer; Bautil, Bruno; Betts, Michael; Burt, April J.; Chapman, Roselle; Currie, Jock C.; Doak, Naomi; Esteban, Nicole; Liljevik, Anna; Mahoune, Jourdan Terence; Onezia, Catherina; et al. (Marine biology, 2022)
Around the world, declines in the mean size of nesting sea turtles have been reported with concerns of a concomitant decrease in the reproductive output of populations. Here, we explore this possibility using long-term observations of green turtles ( Chelonia mydas ) at Aldabra Atoll, Seychelles. Based on > 4500 individual measurements over 21 years (1996–2016), we found the curved carapace length of nesting females declined by about 0.64 cm per decade, from 111.43 to 110.08 cm. For 391 individuals that were measured more than once with measurement interval of 2.8–19 years apart, the mean growth rate was 0.14 cm year −1 . Comparisons between the size of adult females and males were based on 23 and 14 weight measurements, 107 and 33 carapace length measurements and 103 and 33 carapace width measurements, respectively, taken during 1981–1983. Adult females were larger than males, with the sexual dimorphism index, i.e. the ratio of size of the larger sex to the smaller, being 1.09 and 1.10 for carapace length and width, respectively, and 1.25 for weight. Smaller females tended to lay fewer eggs per clutch but the decrease in female mean size was accompanied by increases in numbers of turtles nesting annually, such that the estimated total numbers of eggs per year increased from 1.3 million to 2.0 million between 1996 and 2016. Therefore, a decrease in mean size of nesting females has not compromised egg production for this population.